Dietary almonds and peanuts improve metabolic health and reduce oxidative stress in wistar rats - Mukhtar, Diniwati; Rahmah, Nunung Ainur; Royhan, Aan; Yusnidar, Amirah (Science Midwifery, 2025)
Metabolic syndrome characterized by insulin resistance, atherogenic dyslipidemia, and hypertension, is a significant health concern often associated with obesity and Diabetes Mellitus. Regular consumption of nuts has been suggested to mitigate some of these conditions. This study investigates the effects of almond and peanut consumption on oxidative stress, plasma lipids, body weight, glucose, and blood pressure in Wistar rats. Wistar rats were divided into four dietary groups: standard diet (ST), high-fat diet (HF), high-fat diet with almonds (HFA), and high-fat diet with peanuts (HFP). The treatment lasted for 8 weeks, during which body weight was monitored weekly. Blood pressure measurements and retro-orbital blood samples were collected before and after the treatment. Superoxide dismutase (SOD) and malondialdehyde (MDA) levels were measured using ELISA and TBARS methods. Blood lipid profiles and glucose levels were analyzed using enzymatic methods. Statistical tests used the oAnova followed by Posthoc LSD. The HF group exhibited significant increases in body weight, blood glucose, cholesterol, triglycerides, MDA, and blood pressure, with reduced SOD levels. Conversely, the HFA and HFP groups showed moderated increases in these parameters compared to the HF group. Both nut-supplemented groups had significantly lower MDA levels and higher SOD activity, indicating reduced oxidative stress and enhanced antioxidative defenses. Almonds and peanuts can reduce body fat, improve lipid profiles, and stabilize blood glucose levels, suggesting their potential role in promoting metabolic health and reducing cardiovascular risk. Further research should explore the long-term benefits and the specific bioactive compounds responsible for these effects.